«Լորիկ» ավանդական հարսնագովքերը Կոմիտասի ձայնագրություններում - Տիգրանյան Մարիաննա (Կոմիտասի թանգարան-ին-տ. հրատ.)
Հայկական ժողովրդական երգաստեղծության մեջ եզակի չեն այն օրինակները, որոնք ժամանակի ընթացքում կորցնելով իրենց ֆունկցիոնալ դերն ու նշանակությունը, կամ էլ հակառակը` ձեռք բերելով նորը, մի ժանրից մյուսին են անցել և տեղայնացել: Որքանո՞վ է երգային կամ պարային օրինակը պատկանում այս կամ այն ժանրին. ժանրային դասակարգման հարցում երգային օրինակի ո՞ր կառուցողական (մեղեդային, տաղաչափական) սկզբունքով առաջնորդվել: Այս առումով հետաքրքրություն են ներկայացնում Կոմիտասի «Լորիկ»- ների ձայնագրությունները, որոնք հայկական գեղջկական երգաստեղծության փայլուն օրինակներից են: Մեր կատարած ուսումնասիրությունները, ինչպես նաև ազգագրական այլ աղբյուրներում զետեղված նույնատիպ երգային օրինակների հետ համեմատական աշխատանքների վերլուծություններն ապացույց են այն բանի, որ նշված երգերի եղանակները ոչ թե «մեկից մյուսի զարգացումը ցույց տվող օրինակներն են», այլ մեկ ամբողջական ավանդական ծիսական հարսնագովք: Ժամանակի քայքայիչ ազդեցությամբ, աղճատվելով և մասնատվելով, այդ երգերը, այնուամենայնիվ, պահպանել են իրենց մեղեդային ինքնությունը: Միայն ծիսական երգերի ավանդականությամբ կարելի է բացատրել «Լորիկ»-ներում առկա մետրառիթմական, տաղաչափական և մեղեդային տիպական մտածողությունը, որը բխում է հարսանեկան երգերի բանաձևային կառուցողական սկզբունքից: В армянском народном песнетворчестве не единичны примеры, когда песня, теряя свою функциональную значимость и принадлежность, или наоборот – приобретая новые – из одного жанра переходит в другой. Жанровая “двоякость” присуща некоторым любовно-лирическим песням, которые можно причислить также к свадебным обрядовым песням (восхваление невесты). В таких случаях проникновение интонационных особенностей одного жанра в другой – более чем естественно. Большой интерес представляют комитасовские записи песни “Лорик” (Перепелка), которые являются прекрасным примером армянского народного песнетворчества. Название “Лорик” условно (в рефрене-запеве доминирует “Лорик, лорик”), так как сам Комитас записанные им песни, как правило, озаглавливал первой строчкой, хотя в записях этнографов-музыкантов более старшего поколения варианты рассматриваемой нами песни озаглавлены именно “Лорик”. В одной из своих статей, отмечая песни “Пошел я в поле, поймал перепелку”, “Утра добрый свет”, “Поутру перепелка на поле прилетела” и, рассматривая их в разных жанрах, Комитас приводил их как пример мелодического развития и перехода из одного в другой. Наши исследования, сравнительный и детальный анализ собранного нами обширного песенного материала доказывают идентичность строения музыкального языка этих песен, а также их единую жанровую принадлежность к свадебному обряду The Armenian tradition of folk song creation has numerous examples, when the songs losing their functional role and significance within the course of time, or, on the contrary, obtaining new functions and applications, have transferred from one genre to the other and localized there. How is a song or a dance classified under a genre? What is the structural (melodic, prosodic) principle to be guided by when defining a genre for a song? A kind of duality in genres is typical to some lyrical and love songs, which can be classified into a number of bride-epithalamium songs. In this case, the penetration of typical phrases of one genre into the other is natural. In this regard, Lorik songs transcribed by Komitas, being brilliant examples of Armenian peasant songs, are especially interesting. The title Lorik is conditional (each song ends with the refrain Lorik, lorik, lorik) and includes the songs Gatsi arter, brni lor (I went to the fields, I caught a quail), Aravotun bari lus (Good morning), and Aravot lor mtav art (A quail came into the field in the morning). Komitas mentioned that those songs were examples of transition from one genre to the other. He classified them into two different genres: wedding song and lyrical song. When singing lyrical and love songs, the folk singer manifests his/her inner world and his personal approach using emotion born in a certain situation and typical only to that particular performer. The wedding songs, by contrast, concentrate and save features typical to national traditional songs, which have been accumulated through centuries. My explorations, as well as the comparative analyses of similar examples in other ethnographic sources demonstrate that the melodies of the above-mentioned songs are not just a transformation from one genre into another, but are rather a complete set of traditional ceremonial epithalamiums to the bride. Despite the distortions and disintegrations over time, these songs have maintained their melodic individuality. The metro-rhythmic, prosodic and melodic features typical to the Loriks can be explained only by the “traditionality” of the ceremonial songs, which derive from the formulaic structure pertinent to wedding songs.
Keywords: Հայ երաժշտական ֆոլկլորագիտություն; Թանգարաններ; Կոմիտաս Վարդապետ